Merging Automobile Insurance Regulatory Bodies: The Case of Atlantic Canada - Boyer, Martin; Schiller, Jörg (Assurances et gestion des risques / Insurance and Risk Management, 2004)
The recent automobile liability insurance crisis in Atlantic Canada has prompted the four provincial legislations (Newfoundland and Labrador, New Brunswick, Nova Scotia and Prince Edward Island) to setup a task force to redesign, if necessary, the personal automobile insurance System. After reviewing some of the most interesting new regulatory changes, our paper proposes a new area of discussion: The merger of the four provincial insurance regulatory bodies to combat insurance fraud. We base our paper on the principle that recent premium increases are mainly due to an increase in insurance fraud. We show that merging the regulatory bodies may reduce insurance fraud if the merger allows savings on the average audit cost and on the development of better fraud detection technology. Finally, we suggest a fraud reducing insurance taxation scheme to finance insurance fraud investigations.